New sample holder geometry for high precision isotope analyses. (5th June 2012) - Peres, P.; Kita, N. T.; Valley, J. W.; Fernandes, F.; Schuhmacher, M.
<x xml:space="preserve">Abstract</x> Secondary ion mass spectrometry is applied to a wide range of Geoscience applications because of its capability to provide direct in situ measurement of elemental and isotopic composition. The CAMECA IMS 1280 and 1280‐HR are large geometry ultra‐high sensitivity ion microprobes that provide excellent precision and reproducibility for isotope ratio measurements. A precision at the tenth permil level is routinely achieved for the measurement of 18O/16O ratio from 10 µm spots using multicollection Faraday Cups. However, analytical artifacts related to the surface topography and to the location of the analysis in the sample (X–Y effects) are known to bias the precision for isotope analysis. The X–Y effects have been investigated using a CAMECA prototype sample holder design. Results show a significant improvement in terms of reproducibility for analyses performed over a large area of the sample. Detailed analytical data using the new sample holder will be presented. Copyright © 2012 John Wiley & Sons, Ltd.